Lithological characteristics and formation conditions of lower jurassic limestones occuring in the Patil mountain (south-western Crimea) - G. V. Agafonova; A. O. Andruhovich; V. N. Komarov; E. V. Rakhimova; A. V. Turov (Известия высших учебных заведений: Геология и разведка)
Background. In this article, we investigate an outcrop of the Lower Jurassic limestones of the Eskiorda suite located on the northern slope of the Bodrak River basin in the south-western Crimea.Aim. The outcrop under study is mentioned in the majority of monographs devoted to the geology of the Crimean Mountains. Although the palaeontology of this assemblage has been sufficiently studied, its lithological aspects require elucidation. We carried out a series of lithological studies to identify the composition, structure and formation conditions of this limestone assemblage.Materials and methods. A macroscopic study of the outcrop was conducted followed by a detailed lithological study of collected limestone samples using a polarising microscope.Results. The conducted microscopic analysis revealed three structural types: organogenic-detrital, detrital and oolitic-organogenic-detrital limestones. The dominant component in the composition was fragments of echinoderms, mainly crinoids. Among other components were — in descending order — brachiopods, gastropods, foraminifera, remains of green algae, sponges, ostracods, ammonites and radiolarians, whose total content did not exceed 10%. Cinoid fragments were round to a various degree. The limestone fragments (intraclasts) were characterised by organogenic-clastic and pelitomorphic structures with an organogenic sludge, occasionally containing fine-sandy and silty quartz admixtures. Oolitic-organogenic-detrital limestones were almost entirely composed of crinoid fragments, some of which represented oolith cores. A specific feature of the limestones under study is their significant hardness resulting from the cementation of the structural components predominantly with crustification cement of several generations.Conclusions. The obtained results allowed us to draw conclusions about the formation conditions of the studied rocks. The limestones were formed in shallow water under the action of waves on the sediment in zones of constant currents. The hydrodynamic action on the sediment led to the formation of intraclasts. The early lithification of the sediment contributed to the formation of a hard seabed, on which subsequent generations of echinoderms settled, lived and died, forming an accumulative carbonate body.